A Review and Breakthrough of the Development of Sports Tourism in Xinjiang under the Belt and Road Initiative - Zhang, Zhongchen; Huang, Xiaoling (Journal of Education, Health and Sport, 2025)
With the growing pursuit of a healthy lifestyle, sports tourism has become an integral part of people’s lives. However, sports tourism in China currently accounts for only 5% of the tourism market, while in developed countries, the proportion reaches 25%. This indicates that there is still significant room for growth in China’s sports tourism market. The Belt and Road Initiative proposed by China has had a significant impact on politics, economics, culture, tourism, and other areas. As the gateway to Belt and Road construction, Xinjiang will experience a tremendous boost in its sports tourism industry due to this initiative. This paper employs methods such as literature review, statistical analysis, and SWOT analysis to examine the development of sports tourism in Xinjiang over the past decade under the Belt and Road Initiative, exploring new driving forces for the high-quality development of Xinjiang’s sports tourism industry. Based on this, it proposes approaches such as driving new productive forces, multi-dimensional empowerment, adhering to the right principles while innovating, improving quality and efficiency, and promoting integrated development, in order to break through the development bottleneck of sports tourism in Xinjiang.